SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN JUMLAH PRODUKSI ROTI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDY KASUS : TOKO D’LEG CAKE & BAKERY) - Galang Kukuh Ananda; Maulana Ardiansyah (Journal of Research and Publication Innovation, 2023)
Please write the Abstract in English and Abstrak in Bahasa Indonesia, each of which contains around 160-250 words. The industrial sector in a company, especially those engaged in the industrial sector, cannot be separated from a problem, namely the existence of an increasingly competitive level of competition. This competition forces companies to be able to adjust marketing strategies or productivity in order to survive and even have to increase the amount of production. Production itself is an effort or activity to add value to an item. The direction of activity is aimed at efforts to make arrangements which in nature can add to or create the use of an item or possibly a service. At the D'leg Cake & Bakery Shop, it is a home industry company operating in the food sector in the form of bread, the company produces bread with variants of white bread, bread sweet combination, sweet bread filled with chocolate, sweet bread filled with cheese, sweet bread filled with milk, sweet bread filled with nuts and wheat bread. Based on the number of requests obtained, it can be seen that there is uncertainty about the number of requests from the public as consumers. Based on the uncertainty of the number of requests which also results in uncertainty in producing bread. In this study, the authors used a system development method, namely the Simple Additive Wighting (SAW) method. This method was chosen because the basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes.